1984
DOI: 10.1901/jeab.1984.41-291
|View full text |Cite
|
Sign up to set email alerts
|

Interresponse‐time Punishment: A Basis for Shock‐maintained Behavior

Abstract: Lever pressing of squirrel monkeys postponed brief electric shock according to a freeoperant shock-postponement procedure. Pressing also produced shock with a probability proportional to the duration of the current interresponse time in some conditions, or to the fifth ordinally-preceding interresponse time in others. These conditions provided equal frequencies and temporal distributions of response-produced shocks either contingent on or independent of the current interresponse-time duration, respectively. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 21 publications
6
38
0
1
Order By: Relevance
“…It has been suggested by Galbicka and Branch (1981) (Galbicka & Branch, 1981;Galbicka & Platt, 1984 well maintained for 1 of our monkeys (see Figure 6) under the Fl 5-min DRH:shock schedule. Thus, in all conditions examined here, only responses that met the IRT criterion were suppressed.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has been suggested by Galbicka and Branch (1981) (Galbicka & Branch, 1981;Galbicka & Platt, 1984 well maintained for 1 of our monkeys (see Figure 6) under the Fl 5-min DRH:shock schedule. Thus, in all conditions examined here, only responses that met the IRT criterion were suppressed.…”
Section: Discussionsupporting
confidence: 72%
“…These effects on responding may have been due either to differential punishment of IRTs or to differential negative reinforcement of IRTs by shock-frequency reduction. Galbicka and Platt (1984) controlled for shockfrequency reduction, and, therefore, attributed the increase in rates they observed to the explicit punishment of long IRTs. In the absence of such a control, no choice can be made between these aversive control functions.…”
Section: Discussionmentioning
confidence: 99%
“…Two additions to this list that I find particularly relevant involve studies on shock-maintained behavior, and ones employing Platt's percentile reinforcement schedules. I and others have demonstrated that the effectiveness of local relations can be so powerful as to confound the apparent function of stimuli at the more molar level, as when differential IRT punishment contingencies generate reinforcement-like effects in procedures in which lever pressing is maintained by contingent presentation of electric shock (e.g., Galbicka & Platt, 1984;Lawrence, Hineline, & Bersh, 1994). Stimulus function is not altered under these procedures (i.e., shock does not get transformed into a positive reinforcer; see Pitts & Malagodi, 1991, for a particularly elegant analysis); rather, the behavioral unit that gets differentiated is diametrically opposed to pressing, such that the functional effect appears to be reversed (i.e., by suppressing long IRTs through punishment, lever-press rates increase).…”
Section: Gregory Galbicka Walter Reed Army Institute Of Researchmentioning
confidence: 99%
“…New procedures designed to illuminate the local dynamics of behavior have also become more commonplace. Linear-IRT schedules (Galbicka & Platt, 1984;Platt, 1979;Weiss, 1970), cyclic-interval schedules (Innis & Staddon, 1971;McDowell & Sulzen, 1981;Staddon, 1964), percentile schedules (Arbuckle & Lattal, in press;Galbicka, Fowler, & Ritch, 1991;Galbicka & Platt, 1986, 1989Machado, 1989), and concurrent schedules for response sequences (e.g., Fetterman & Stubbs, 1982), among others, all provide reinforcement dynamically as a function either of ongoing behavior or of time, to control the rate of change of overall reinforcement frequency. In some cases (e.g., percentile, linear IRT), the rate of change is zero, holding the aggregate reinforcement rate constant throughout the session while varying reinforcement for particular extended sequences of behavior.…”
Section: The Dynamics Of Behaviormentioning
confidence: 99%